Association of RAAS inhibitors on osteoporosis and fracture risk in the hypertensive population–A prospective population-based cohort study in Lanzhou, China - Yin, Hongtao; Yang, Mengdi; Sun, Weiming; Zhang, Ruixing; Zhen, Donghu; Tang, Xulei (BMC musculoskeletal disorders, 2024)
Renin-angiotensin-aldosterone system (RAAS) inhibitors appear to benefit bone tissue in antihypertensive treatment. However, the association between RAAS inhibitors and bone metabolism was inconsistent. Based on the study of Risk Evaluation of Cancers in Chinese Diabetic Individuals(REACTION) conducted in 2011, We followed 6,252 Lanzhou residents aged 40-75 years from 2014 to 2016. Finally, 1,625 hypertension cases with complete data were included in the analysis. The study subjects were divided into four groups according to the type of antihypertensive drugs. We employed logistic or multivariate Cox proportional hazards regression to estimate the association between different antihypertensive drug use and osteoporosis, the risk of fracture, and the change in bone mineral density (BMD) level. The association of osteoporosis or the fracture risk by cumulative duration of use of these medications (< 3 years.) and (> 3 years.) was also estimated. The cross-sectional study showed that there was no significant association between baseline antihypertensive drugs (angiotensin-converting enzyme inhibitors (ACEI) and angiotensin receptor blockers (ARB)) use and osteoporosis and fracture. During a mean follow-up of 3.4 years in the longitudinal study, there were 478 new osteoporosis cases and 76 fractures. Compared with patients without antihypertensive drug use, the hazard ratios (HRs) [95% confidence interval (CI)] for the risk of osteoporosis were 1.005(0.651,1.552) and 1.077(0.793,1.462) in ACEI or ARB use (p > 0.05). ACEI or ARB use was also not significantly associated with fracture risk (HR 1.102(0.326,3.726), 0.735(0.251,2.148), p > 0.05). Further analysis showed that the use of ACEI (HR 1.078(0.146,7.950)) or ARB (HR 1.169(0.347,3.939)) was not significantly associated with the improvement of osteoporosis (p > 0.05). In addition, the duration of RAAS inhibitors used showed no apparent correlation with the risk of osteoporosis (≤ 3 years: HR 0.872 (0.516, 1.474), > 3 years: HR 1.151 (0.574, 2.308)), nor with the improvement of osteoporosis and the risk of fracture. Meanwhile, the association mentioned above did not change compared to different RAAS inhibitors. The use of RAAS inhibitors, including ACEIs and ARBs, was not significantly associated with osteoporosis, risk of fracture, or BMD change.